Effectiveness of Intermittent Normal Saline Flush to Maintain the Patency of Intravenous Cannula among Children Admitted in Pediatric Wards of Tertiary Center of Eastern Nepal - Belbase, Geeta; Bhandari, Sunita; Karn, Basanta Kumar; Yadav, Upendra; Chaudhary, Ramanand (Annapurna Journal of Health Sciences, 2023)
Introduction: Insertion of peripheral intravenous cannula in children is a stressful experience. Nurses caring for neonates and infants spend a significant amount of time starting and managing intravenous (IV) cannula. It is therefore desirable to maintain the patency as long as possible once cannula is inserted. To achieve this cannula can be infused with fluid at a low rate or flushed intermittently. This study was done to assess effectiveness of intermittent normal saline flush to maintain the patency of intravenous cannula among children of pediatric ward. Methods: An Experimental study was conducted on 60 samples, 30 in each in control and experimental group. Study was conducted among children of age group 5-14 years undergoing Intravenous cannulation during the time of data collection was 3 months. Consecutive sampling technique was used and random allocation of two groups i.e. control group and experimental group was done by lottery method. The data was collected by assessing the patency of intravenous cannula twice a day, before giving medication for three consecutive days. Results: More than half 56.7% and 43.3% of children in the experimental group were 5-9 years and 10-14 years respectively whereas 60% and 40% of the children in the control group were 5-9 years and 10-15 years respectively. In experimental group patency was maintained in all cannula till day 2 and 56.7% cannula remained patent up to the day 3 evening. While in control group, patency decreased from day 2 morning (73.3%) and only 3.3% cannula were patent in day 3 evening. The difference in patency was highly significant (p<0.001) between two groups. Conclusion: Intermittent normal saline flush was found to be highly effective for maintaining patency of intravenous cannula. Size of cannula was not homogenous in both groups but it does not show any statistical significance in patency of cannula. Age, sex, medicine, diagnosis and site of the cannula were not associated with patency of intravenous cannula.